Effect of C2H2 flow rates and microwave powers on the synthesis of sp3 carbon on glass substrates - Prem Thongchai (2018)
© 2015, Hanyang University. All rights reserved. In this research, sp3 and sp2 carbon was deposited on glass substrates in 10-100 ml/min flow rates of C2H2 at 650, 750 and 900 W microwave for 5 sec each. Raman analysis revealed the presence of sp3 and sp2 carbon at 1534-1599 and 1325-1377 cm−1, corresponding to the G and D bands, respectively. Both sp3 and sp2 contents were controlled by the C2H2 flow rates and microwave powers. By using X-ray diffraction (XRD), selected area electron diffraction (SAED), atomic force microscopy (AFM) and scanning electron microscopy (SEM), the carbon films of nanoparticle colonies were detected.